Demonstrating lexical competence in language use - Mohamed Ali, Haja Mohideen (British Journals, 2012)
Lexical competence is that aspect of communicative competence that deals with knowledge of lexical or vocabulary items and their meaning and the ability to use them appropriately. It is generally well known that without grammatical accuracy, an utterance may be understood, but without precise vocabulary, it is indeed difficult. Lexis belongs to the level of language which concerns lexical items or content words in a language. Generally while grammar deals with closed word classes such as the preposition, pronoun, determiner, conjunction and the primary and modal auxiliaries, lexis involves the four open word classes which are the noun, adjective, lexical verb and adverb. Lexical word classes are known as open classes because new words can continually be added to them. In the field of science, technology, politics and economics, for instance, new expressions are being coined all the time for hitherto unknown concepts and inventions. In the area of politics new words are introduced in association with leaders and their policies. But many of these political expressions go out of circulation when the leaders are not around or when they fall from grace. In the world of food and drink, new exotic words appear so very often that it is almost impossible to keep track of all the new coinages. Acquiring lexical competence must be conceived as a relational process which requires learners to make friends with the words of the target language (Morgan and Rinvolucri, 1985: 5).